Dielectric inorganic composition
By adjusting the ratio of A to M in the oxide crystal, the problem of the dielectric constant of the existing dielectric materials at high temperatures is solved, and a dielectric with a high dielectric constant and stable temperature is realized, which is suitable for high-temperature capacitor applications.
Patent Information
- Application Number
- CN202080024098.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-08
- Filing Date
- 2020-03-23
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-03-23
AI Technical Summary
The dielectric constant of existing dielectric materials decreases in high temperature environments, which cannot meet the requirements of capacitors for dielectric constant and temperature stability at high temperatures.
By adjusting the ratio of A to M in the oxide crystal (A is P, Ge and V, M is Nb and Ta), the dielectric constant is set above 500 and is maintained within the temperature range of -50°C to 350°C. Stablize.
It realizes a dielectric with a high dielectric constant and small variations over a wide temperature range, and is suitable for capacitor applications in high temperature environments.
Smart Images

Figure CN113631509B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an inorganic composition having properties that can be used as a dielectric, and more specifically, to an inorganic composition having a high dielectric constant and a small rate of change of the dielectric constant in the range of -50°C to 350°C, and a dielectric using the same. Background Art
[0002] As electronic devices such as smartphones and tablets become more popular, electronic components used in these electronic devices are required to be smaller and more high-performance. As a result, multi-layer ceramic capacitors (MLCC) used as multi-layer capacitors are also required to be smaller and have higher capacitance.
[0003] In recent years, with the popularization of electric vehicles, the purpose of improving motor performance and compactness requires that electronic assembly substrates be directly installed on the high-temperature motor periphery. With the high temperature of the use environment of vehicle-mounted electronic assembly components, MLCC is also required to have high electrostatic capacitance and good capacitance temperature characteristics even at higher temperatures (200°C to 350°C). In other words, the dielectric constituting the capacitor is required to have a high dielectric constant even in a high temperature range exceeding 200°C, and the dielectric constant has little change with temperature.
[0004] In addition, in recent years, there has been an increasing demand for capacitors with high energy storage density used in semiconductor processing, excimer lasers used in vision correction surgery, medical X-rays, power storage devices, power transmission equipment, etc. In order to obtain energy storage density for the dielectric used in such capacitors, it is required to have both high dielectric constant and high dielectric breakdown strength, and it is also required that the temperature change of the capacitor is small at high temperatures.
[0005] However, BaTiO3, which is often used as a dielectric, has a Curie temperature of about 130°C, so the dielectric constant decreases significantly in the temperature range above 150°C, and there is a problem that it cannot meet the above requirements.
[0006] Patent Document 1 states that the Curie temperature of a BaTiO3 composite can be increased to obtain good temperature characteristics of capacitance up to 200°C, but the dielectric constant of this material is below 500, and thus a large capacitance cannot be obtained.
[0007] In addition, KNbO3 and K 0.5 Na 0.5NbO3, etc. However, during the firing process of these dielectric materials, potassium (K) will scatter (sublimate), and the resulting dielectric material will have lattice defects, thereby causing problems such as reduced insulation. Here, if the insulation is reduced, it is easy to cause dielectric breakdown due to semiconductorization. Therefore, when the above-mentioned dielectric materials are applied to ceramic electronic components such as capacitors, there is a problem of reduced reliability of the ceramic electronic components. In addition, the scattering of potassium (K) makes it difficult to manage the production process, which is not a good situation in which productivity is reduced.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent document 1: Japanese Patent Application Publication No. 2017-119607. Summary of the invention
[0011] Problem that the invention aims to solve
[0012] The present invention aims to solve the above-mentioned problems. That is, the present invention aims to provide a dielectric having a high dielectric constant and a stable temperature dependence up to a high temperature range.
[0013] Solutions for solving problems
[0014] In order to solve the above-mentioned problems, the inventors have made intensive research and found that in an oxide crystal containing A and M (A is one or more of P, Ge and V, and M is one or more of Nb and Ta), by setting the ratio of A to M in the range of 0.01 to 1.00, the dielectric constant is thereby increased to more than 500, thereby completing the present invention.
[0015] The present invention comprises the following (1) to (6).
[0016] (1) An inorganic substance, characterized in that it contains oxide crystals containing A and M, wherein A is one or more of P, Ge and V, and M is one or more of Nb and Ta, and the ratio of A to M is in the range of 0.01 to 1.00, and the dielectric constant of the inorganic substance is greater than 500.
[0017] (2) The inorganic substance according to (1) above, wherein the temperature change rate of the dielectric constant in the range of -50°C to 350°C is 30% or less.
[0018] (3) The inorganic substance according to (1) or (2) above, characterized in that the oxide crystal is PNb9O 25 , P 2.5 Nb 18 O 50 and GeNb9O25 ,GeNb 18 O 47 ,GeNb 19.144 O 50 、VNb9O 25 、VNb9O 24.9 ,PTa9O 25 、GeTa9O 25 、VTa9O 25 and one or more of their solid solutions.
[0019] (4) A dielectric comprising the inorganic substance according to any one of (1) to (3).
[0020] (5) The dielectric according to (4) above, characterized in that it is a ferroelectric.
[0021] (6) A capacitor comprising the dielectric described in (4) or (5) above.
[0022] Effects of the Invention
[0023] According to the present invention, a dielectric having a high dielectric constant and excellent temperature characteristics in a temperature range of -50°C to 350°C, and a ceramic capacitor including the dielectric can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The diagram shows the XRD patterns of Example 1 and Example 2.
[0025] Figure 2 Graph showing the relationship between the dielectric constant and the frequency of Example 1 and Example 2.
[0026] Figure 3 Graph showing the relationship between the dielectric constant and temperature in Example 4.
[0027] Figure 4 This is a diagram showing the hysteresis curve of Example 4.
[0028] Figure 5 Graph showing the relationship between the dielectric constant and the frequency in Example 5.
[0029] Figure 6 Graph showing the relationship between the dielectric constant and temperature in Example 5.
[0030] Figure 7 Graph showing the relationship between the dielectric constant and the frequency in Example 6.
[0031] Figure 8 Graph showing the relationship between the dielectric constant and temperature in Example 6. DETAILED DESCRIPTION
[0032] <Dielectric material of the present invention>
[0033] The inorganic composition of the present invention will be described.
[0034] The inorganic composition of the present invention is useful as a dielectric, and is a ceramic containing oxide crystals containing A and M (A is one or more of P, Ge and V, and M is one or more of Nb and Ta). By adjusting the ratio of A to M, a dielectric constant of 500 or more and a dielectric constant with little change over a wide temperature range of -50°C to 350°C can be achieved. In order to obtain excellent dielectric properties, the ratio of A to M is preferably in the range of 0.01 to 1.00, more preferably in the range of 0.03 to 0.50, and most preferably in the range of 0.04 to 0.20. Among the aforementioned oxide crystals containing A and M, PNb9O 25 , P 2.5 Nb 18 O 50 and GeNb9O 25 ,GeNb 18 O 47 ,GeNb 19.144 O 50 、VNb9O 25 、VNb9O 24.9 ,PTa9O 25 、GeTa9O 25 、VTa9O 25 Since the solid solutions thereof have more excellent characteristics, it is preferable to contain them.
[0035] The inorganic composition of the present invention may also contain ingredients other than those mentioned above, such as SiO2, GeO2, B2O3, Al2O3, ZnO, Bi2O3, TiO2, ZrO2, V2O5, Ta2O5, WO3, alkali metal oxides, alkaline earth metal oxides, rare earth oxides, transition metal oxides, etc. These ingredients can play the role of sintering aids, can exist alone, can be dissolved in the above-mentioned crystals, and can also form new crystals with the elements constituting the above-mentioned crystals. By introducing these sintering aids, the dielectric properties can be improved due to the decrease in the firing temperature or the formation of a solid solution.
[0036] Glass may be added to the inorganic composition of the present invention. Glass functions as a sintering aid and has the effect of lowering the sintering temperature.
[0037] The inorganic composition of the present invention can be compounded with other dielectric crystals, such as tungsten bronze crystals, perovskite crystals, CaZrO3 crystals, SrZrO3 crystals, BaTi2O5 crystals, CaTi2O5 crystals, etc. By compounding with these dielectrics, the dielectric properties as designed can be approached. In addition, as the above-mentioned tungsten bronze crystal, it is preferred to include MNb2O6 (M: Ca, Sr, Ba), M2RNb5O 15 (M: Ca, Sr, Ba; R: Na, K), K2LnNb5O 15 (Ln: Y, Ce, Sm, Eu, La, Gd, Tb, Dy, Ho, Bi) crystals and their solid solutions, one or more of the group. As the above-mentioned perovskite crystal, it is particularly preferred to include RNbO3, RTaO3, (Bi 0.5 , R 0.5 )One or more of the group consisting of TiO3 (R: Na, K), MTiO3 (M: Ca, Sr, Ba) crystals and their solid solutions.
[0038] The dielectric constant of the inorganic composition of the present invention at a frequency of 1 kHz to 100 kHz is preferably 500 or more, more preferably 650 or more, particularly preferably 800 or more, and most preferably 900 or more.
[0039] The temperature change rate of the dielectric constant of the inorganic composition of the present invention at 1 kHz and / or 100 kHz is preferably less than 30% in the temperature range of -50°C to 350°C, more preferably less than 20% in the temperature range of -50°C to 350°C, particularly preferably less than 15%, and most preferably less than 10%.
[0040] It should be noted that in the present invention, the dielectric constant and dielectric loss are measured at a frequency ranging from 100 Hz to 1 MHz using an LRC tester (Keysight Technology, 4274A) or an impedance analyzer (e.g., SI1260 manufactured by Solartron), and the values at 1 kHz or 100 kHz are regarded as the dielectric constant and dielectric loss of the present invention.
[0041] When the inorganic composition of the present invention is a dielectric ceramic, it has a high relative dielectric constant and has good temperature characteristics in a wide temperature range of -50°C to 350°C. Therefore, it can be suitably used as a capacitor that can cope with high temperatures. Specifically, it can be used for the operation of SiC or GaN-based power components of automotive components expected to be used in high temperature environments, or for removing noise in the engine room of an automobile.
[0042] Furthermore, since the dielectric using the inorganic composition of the present invention is a ferroelectric and is expected to have good piezoelectric properties (for example, piezoelectric constant: d, electromechanical coupling coefficient: k), it can also be suitably used in a piezoelectric element.
[0043] <Manufacturing method>
[0044] The method for producing the inorganic composition of the present invention will be described.
[0045] First, the raw materials of each component constituting the inorganic composition of the present invention are prepared. The raw materials of each component are not particularly limited, and can be appropriately selected from the oxides, composite oxides, or various compounds (such as carbonates, nitrates, hydroxides, fluorides, organometallic compounds, etc.) of the above-mentioned components that can be converted into their oxides or composite oxides by calcination.
[0046] Next, the prepared raw materials are weighed and mixed so as to have a predetermined composition ratio, thereby obtaining a raw material mixture. Examples of the mixing method include wet mixing using a ball mill and dry mixing using a dry mixer.
[0047] The obtained raw material mixture may be granulated by adding a binder resin to form a granulated product, or may be paste-formed together with a binder resin or a solvent to form a slurry. In addition, the raw material mixture may be pre-calcined before forming a granulated product or a slurry.
[0048] The method for forming the granules or slurry is not particularly limited, and examples thereof include sheet method, printing method, dry molding, wet molding, extrusion molding, etc. For example, in the case of dry molding, the granules are filled into a mold and compressed (pressed) to form. The shape of the molded body is not particularly limited, and can be appropriately determined according to the intended use.
[0049] The obtained molded body can be fired by any method such as normal pressure sintering, hot pressing sintering, hot isostatic pressing (hotisostatic pressing) pressure sintering, spark plasma sintering, microwave sintering, etc. as needed, thereby obtaining a ceramic dielectric. The firing conditions can be appropriately determined according to the firing method and composition, etc. The firing temperature is preferably 800°C to 1400°C, and the holding time is preferably several minutes to 24 hours.
[0050] The fired ceramic dielectric is sometimes heat treated in air, oxygen or reducing atmosphere as needed. Through such heat treatment, defects are reduced and the dielectric properties of the dielectric are improved. Preferably, the heat treatment temperature is in the range of 700°C to 1200°C and the treatment time is in the range of 1 hour to 24 hours.
[0051] The ceramic dielectric composed of the inorganic composition of the present invention produced in this manner can be suitably used in electronic components such as capacitors.
[0052] The above shows a method for producing a disc-shaped ceramic dielectric composed of the inorganic composition of the present invention, but a ceramic capacitor constituting a dielectric layer of a laminated electronic component can also be produced by a green body method, etc. That is, the dielectric powder of the present invention can be made into a paste, and a dielectric green body layer can be formed on a carrier film by a doctor blade method, etc., and an internal electrode layer paste can be printed thereon in a predetermined pattern, and then these can be peeled off layer by layer, laminated, and then pressure is applied to form an integral body, and finally fired at a temperature of about 800°C to 1200°C, thereby producing a ceramic capacitor.
[0053] In addition, the inorganic composition of the present invention can be used to make a thin film dielectric by using a common thin film forming method. For example, a vacuum deposition method, a high frequency sputtering method, a pulsed laser deposition method (PLD; Pulsed Laser Deposition), an MOCVD (Metal Organic Chemical Vapor Deposition) method, an MOD (Metal Organic Decomposition) method, a gel sol method, a hydrothermal method, etc. can be used to form a thin film dielectric.
[0054] Therefore, the inorganic composition of the present invention can be used for electronic components such as single-plate capacitors, electronic components such as laminated capacitors, and thin-film electronic components, or piezoelectric elements.
[0055] Example
[0056] Hereinafter, the present invention will be described in more detail using examples, but the present invention is not limited thereto at all.
[0057] <Production of Examples 1 to 4>
[0058] An inorganic composition containing oxide crystals containing P and Nb is prepared by spark plasma sintering in the following order. First, the powders of NH4H2PO4 and Nb2O5 as raw materials are mixed in a predetermined ratio (P / Nb=0.11), filled into a polyethylene mortar together with zirconium oxide balls with a diameter of 2 mm and ethanol, mixed for 24 hours, and dried for 24 hours. The dried mixed powder is pre-fired at 1000°C for 2 hours. The pre-fired product obtained is mixed, crushed, and dried under the same conditions as above to obtain a dielectric powder composed of an inorganic composition. Take 4g of the dielectric powder, fill it in a graphite mold with an inner diameter of 20mm, and use a spark plasma sintering device (Sumitomo Coal Mining Co., Ltd. SPS625) to apply a pressure of 35MPa in the up and down directions in a vacuum atmosphere while keeping it at 1050°C to 1200°C for 5 minutes to 12 minutes, thereby obtaining a disc-shaped dielectric. The obtained disc-shaped dielectric was polished on both sides and then heat treated at 1000° C. for 4 hours while oxygen was flowing at 1 L / min to obtain a sample for evaluating physical properties. Table 1 shows the production conditions and physical properties of the examples.
[0059] Figure 1 The XRD patterns of Example 1 and Example 2 are shown in FIG. Since all the diffraction peaks are attributed to PNb9O 25 It can be seen that the ceramic dielectric is composed of PNb9O 25 The XRD pattern was measured using an X-ray diffractometer (manufactured by Philips, trade name: X'Pert-MPD).
[0060] Figure 2 The frequency dependence of the dielectric constant of Example 1 and Example 2 is shown in FIG. 1. In addition, the dielectric constant and dielectric loss were measured at room temperature (25°C) using an impedance analyzer (SI1260 manufactured by Solartron) after gold electrodes were deposited on both sides of the sample. As can be seen from this figure, within the measured frequency range (100 Hz to 10 6 Hz), the dielectric constant was above 900 and did not change significantly with the frequency. In addition, the dielectric loss was confirmed to be as small as 5% or less in the above frequency range.
[0061] The temperature dependency of dielectric properties was measured using an LCR meter at a frequency of 100 Hz to 100 kHz and a temperature range of -30°C to 350°C. Figure 3 The measurement results for Example 4 as a representative example are shown in FIG. It is the result of plotting the dielectric constant and temperature at a frequency of 100 kHz. As can be seen from this figure, although the dielectric constant of the dielectric of the present invention shows a high value, it does not change significantly within the temperature range of -30°C to 350°C.
[0062] The rate of change of dielectric constant with temperature (ε T ) When the dielectric constant at 25°C is used as a reference, the degree of change in the dielectric constant at each temperature is determined and calculated using the following formula.
[0063] ε T (%) = [(dielectric constant at target temperature - dielectric constant at 25°C) / dielectric constant at 25°C] × 100%
[0064] The change rate (ε) of the dielectric constant of Example 4 obtained from the above formula T ) is shown in Figure 3 From this, it can be seen that the rate of change of the dielectric constant is 25% or less in the temperature range of -30°C to 350°C, and is 10% or less in the temperature range of -30°C to 250°C.
[0065] [Table 1]
[0066]
[0067] Figure 4 The electric field-polarization curve of Example 4 is shown. As can be seen from this figure, the present dielectric is a ferroelectric.
[0068] <Preparation of Example 5>
[0069] An inorganic composition containing oxide crystals containing Ge and Nb is prepared by spark plasma sintering in the following order. First, the powders of GeO2 and Nb2O5 as raw materials are mixed in a predetermined ratio (Ge / Nb=0.11), and filled into a polyethylene mortar together with zirconium oxide balls with a diameter of 2mm and ethanol. After mixing for 24 hours, dry for 24 hours. The dried mixed powder is pre-calcined at 950°C for 2 hours. The obtained pre-calcined product is mixed, crushed and dried under the same conditions as above to obtain a dielectric powder composed of an inorganic composition. Take 2.5g of the dielectric powder and fill it in a graphite mold with an inner diameter of 15mm. A spark plasma sintering device is used to apply a pressure of 50MPa in the up and down directions in a vacuum atmosphere while keeping the temperature at 900°C for 5 minutes to obtain a disc-shaped dielectric. For the obtained disc-shaped dielectric, after grinding both sides, heat treatment is performed at 850°C for 4 hours while circulating oxygen at 2L / min to obtain a sample for physical property evaluation.
[0070] From the analysis of XRD patterns, it was inferred that GeNb 19.144 O 50 Crystalline phase or GeNb9O 25 Crystal phase. Due to GeNb 19.144 O 50 With GeNb9O 25The diffraction peaks of 2 crystals overlap, so it is possible that two crystals coexist at the same time.
[0071] Figure 5 The frequency dependence of the dielectric constant of Example 5 is shown. It can be seen that the dielectric constant is as high as 4000 to 5000 in the measured frequency range. Figure 6 The relationship between the dielectric properties and temperature characteristics shows that the dielectric constant changes little when exposed to high temperatures above 250°C, and the rate of change in the dielectric constant is less than 15%.
[0072] <Preparation of Example 6>
[0073] An inorganic composition containing oxide crystals containing Ge and Nb is prepared by a conventional sintering method in the following order. First, the powders of GeO2 and Nb2O5 as raw materials are mixed in a predetermined ratio (Ge / Nb=0.11), and filled into a polyethylene mortar together with zirconium oxide balls with a diameter of 2 mm and ethanol. After mixing for 24 hours, dry for 24 hours. The dried mixed powder is pre-fired at 950°C for 2 hours. The obtained pre-fired material is mixed, crushed and dried under the same conditions as above to obtain a dielectric powder composed of an inorganic composition. Take 2.0g of the dielectric powder, fill it in a mold with an inner diameter of 20mm, and after being formed into particles by biaxial pressure, sinter it in an electric furnace in the atmosphere at 1170°C for 4 hours. For the obtained disc-shaped dielectric, XRD is measured and the dielectric constant is measured.
[0074] Since the XRD pattern was the same as that of Example 5, it was found that the same crystal phase was present.
[0075] Figure 7 The frequency dependence of the dielectric constant of Example 6 is shown. It can be seen that the dielectric constant is approximately constant at about 700 within the measured frequency range. Figure 8 The relationship between the dielectric properties and temperature characteristics confirmed that after being exposed to high temperatures above 200°C, the change rate of the dielectric constant was as low as less than 15%, and the dielectric loss was less than 0.5.
Claims
1. An inorganic substance, characterized in that It consists of PNb9O 25 、GeNb9O 25 ,GeNb 19.144 O 50 The inorganic substance is composed of one or more oxide crystals in a solid solution thereof, the dielectric constant of the inorganic substance is 900 or more, and the temperature change rate of the dielectric constant in the range of -50°C to 350°C is 30% or less.
2. A dielectric comprising the inorganic substance according to claim 1.
3. The dielectric according to claim 2, characterized in that It is a ferroelectric. A capacitor comprising the dielectric according to claim 2 or 3.
Citation Information
Patent Citations
Dielectric body ceramic composition and method for producing the same, and ceramic electronic component
JP2017119607A
Dielectric ceramic composition and electronic component
JP2013028478A
Ferroelectric ceramic and method for producing the same
JP2017178744A
Dielectric body
WO2018092637A1